2020
DOI: 10.3174/ajnr.a6386
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Leukoencephalopathy: A Rare Complication after Coiling of Cerebral Aneurysms

Abstract: BACKGROUND AND PURPOSE: Delayed leukoencephalopathy is a rare complication that occurs after endovascular coiling of cerebral aneurysms. We aimed to describe a clinical picture of delayed leukoencephalopathy and explore potential associations with procedural characteristics. MATERIALS AND METHODS: We considered endovascular coiling procedures for cerebral aneurysms performed between January 2006 and December 2017 in our institution with follow-up MRIs. We used logistic regression models to estimate the ORs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 29 publications
1
36
3
Order By: Relevance
“…The incidence of immune-mediated leukoencephalopathy in patients treated with EVT for intracranial aneurysms was estimated to be between 0.5% and 2.3% in various cohort studies [3][4][5]. Interestingly, the vast majority of the cases were women, aged 41-65 years.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of immune-mediated leukoencephalopathy in patients treated with EVT for intracranial aneurysms was estimated to be between 0.5% and 2.3% in various cohort studies [3][4][5]. Interestingly, the vast majority of the cases were women, aged 41-65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular coiling is an effective technique for treating unruptured, ruptured aneurysms as well as preventing the rupture of cerebral aneurysms. 1 Studies have shown that, after endovascular interventions, a few patients experience complications such as thromboembolic events, aneurysm rupture, and perianeurysmal edema, which may be suggestive of symptomatic inflammatory responses. 1,19,20 Also, reversible encephalopathy syndrome has been observed in patients after endovascular interventions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Studies have shown that, after endovascular interventions, a few patients experience complications such as thromboembolic events, aneurysm rupture, and perianeurysmal edema, which may be suggestive of symptomatic inflammatory responses. 1,19,20 Also, reversible encephalopathy syndrome has been observed in patients after endovascular interventions. 1,21,22 The possible mechanism of CIEP is as a result of disruption of the BBB leading to leakage of contrast agent into the cortex as well as subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations